Digital content marketing : creating value in practice - Krowinska, Agata (United Notion, 2023)
"Digital Content Marketing: Creating Value in Practice introduces the principles of the content marketing discipline and serves as a guide to any professional or student who wants to learn how to successfully plan and implement digital content marketing strategies and tactics. Filled with contemporary examples of the most successful creative content marketing practices, case studies and professional advice from subject experts, this text offers an in-depth view of the world of content marketing from a value-based perspective. The textbook also includes practical advice on content marketing ideation, content management and content curation, as well as offering recommendations for the best content marketing software. The textbook offers a good balance of both theory and practice and is suitable for advanced undergraduate students and postgraduate students studying content marketing, digital marketing or social media marketing. Support material includes an instructor manual, chapter-by-chapter PowerPoint slides and a test bank of exam questions"--